Assembly of CRISPR ribonucleoproteins with biotinylated oligonucleotides via an RNA aptamer for precise gene editing - Jared Carlson-Stevermer (Nature Portfolio, 2017)
Using CRISPR to write specific genetic sequences can sometimes be difficult due to the preference of mammalian cells to repair breaks using NHEJ. Here the authors form nanoparticles to localize the template sequence to the nuclease, shifting repair in favor of HDR.